1996
DOI: 10.1192/bjp.169.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Therapy and Recovery from Acute Psychosis: a Controlled Trial

Abstract: CT appears to be a potent adjunct to pharmacotherapy and standard care for acute psychosis. Issues concerning internal and external validity of the study and opportunities for further research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(142 citation statements)
references
References 0 publications
4
134
1
3
Order By: Relevance
“…Although there were differences between the CBT and control group over 2-year follow-up, including a lower percentage of relapses, time to relapse and days spent in hospital, these differences were not statistically significant. It is possible that the results reported by Drury et al [40, 41 ]were over-optimistic, resulting from an inflated effect size due to inadequate methodology. In spite of these potential difficulties, the study by Drury et al [40, 41] established that CBT could be carried out even with those who were most severely ill, a fact confirmed by Haddock et al [46].…”
Section: The Evidence For Cbt For Schizophreniamentioning
confidence: 55%
See 3 more Smart Citations
“…Although there were differences between the CBT and control group over 2-year follow-up, including a lower percentage of relapses, time to relapse and days spent in hospital, these differences were not statistically significant. It is possible that the results reported by Drury et al [40, 41 ]were over-optimistic, resulting from an inflated effect size due to inadequate methodology. In spite of these potential difficulties, the study by Drury et al [40, 41] established that CBT could be carried out even with those who were most severely ill, a fact confirmed by Haddock et al [46].…”
Section: The Evidence For Cbt For Schizophreniamentioning
confidence: 55%
“…It is possible that the results reported by Drury et al [40, 41 ]were over-optimistic, resulting from an inflated effect size due to inadequate methodology. In spite of these potential difficulties, the study by Drury et al [40, 41] established that CBT could be carried out even with those who were most severely ill, a fact confirmed by Haddock et al [46]. This finding stimulated the Study of Cognitive Reality Alignment Therapy in Early Schizophrenia (SoCRATES) [49, 61] which tested whether CBT delivered during admission for an acute episode of early (first or second episode) schizophrenia would speed recovery and confer resistance to subsequent relapse.…”
Section: The Evidence For Cbt For Schizophreniamentioning
confidence: 55%
See 2 more Smart Citations
“…They found a significant improvement on the PANSS negative symptom scale for both CBT and CR treatments, with no between-group differences, suggesting that both interventions were effective. Drury, Birchwood, Cochrane, and Macmillan (1996) found that people randomly assigned to either group and individual cognitive therapy, or recreation and support therapy (an active control designed to match therapist hours and provide structured activities and informal support) showed comparable improvement in negative symptoms as measured by the Psychiatric Assessment Scale (PAS; Krawiecka, Goldberg, & Vaughan, 1977) after treatment and at the nine month follow-up. Finally, Lewis et al (2002) randomly assigned people in their first or second acute hospital admission for psychosis to five weeks of individual CBT or supportive counseling (a manualized control therapy matched for therapist exposure) and found that those who received CBT had a significant improvement in overall symptoms at post-intervention (negative symptoms results were not reported) compared to those who received TAU (unspecified across participants with the exception that it always included medication and day or inpatient treatment.…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%